Unemployment, Basic and Monetary: The Classical Analysis and the Keynesian - Champernowne, D. G. (Review of Economic Studies, 1936)
Journal Article Unemployment, Basic and Monetary: the Classical Analysis and the Keynesian Get access D. G. Champernowne D. G. Champernowne Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 201–216, https://doi.org/10.2307/2967628 Published: 01 June 1936